The Role of Gen-Z in Supporting Sustainable Development Through Green Economy Towards Golden Indonesia 2045 - Marpaung, Clier Romi; Tsabit, Ilhaam Anggra Za’im; Pangestuti, Irene Rini Demi (Research Horizon, 2024)
Generation Z is currently a generation that has a big influence in determining future direction and policies. They also play a very important role in efforts to achieve the Sustainable Development Goals (SDGs) set by the UN. A green economy can help address environmental and social problems while expanding economic development. By promoting and facilitating the development of a green economy, generation Z can help build a Golden Indonesia 2045. This vision focuses on efforts to make Indonesia a developed and just country by 2045. A green economy can help achieve this vision by expanding economic development while paying attention to environmental balance and social. The method used in this research is the narrative review method. The narrative review method aims to identify and summarize previously published articles, avoid duplication of research, and look for new fields of study that have not been researched. The results of this research, namely the role of generation Z in supporting the SDGs through green economic development, are important and must be accepted as a responsibility. together. They have the ability and potential to lead sustainable development efforts and help achieve a Golden Indonesia 2045.